Managemen and investment of quarry material in Latakia region “AL Badrusiyah quarry care study” - وهبي صالح; حليمة عبد الكريم; مخلوف هنادي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Man s exploitation of any element of the natural environment its initial gtate this means trans for ming it from a natural source to a natural resource , And exploiting it in away that achieves a benefit that goes beyond mere self sufficiency , but rather the reflection of the benefit of its exploitation on others and on the region in a narrow way of securing job opportunities . This is what applies to the materials extracted from the al Badrusiyah quarry (marble, plaster…) as the concerned institution invested and tans fromed it into natural resources that achieve an economic base for the quarry and contribut to its produests to the national economy in general, especially that the quarry products have features and specifications that are required externally and are subject to a well – studied investment management that has future prospects based on research studies and laboratory samples of the quarry.